The Effectiveness of Animation Learning Media in Improving Mastery of Arabic Vocabulary at Madrasah Ibtidaiyah Through Limited Face-to-Face - Qurrotul Aini; Khizanatul Hikmah (Indonesian Journal of Islamic Studies, 2022)
Animated media can be an interesting medium for children and adults who want to learn Arabic vocabulary. Animated media is also very helpful for teachers to attract the attention of students. By bringing up research that discusses animation media, it is hoped that it can help learning Arabic vocabulary at MI Muhammadiyah 2 Kedungbanteng, as well as the effectiveness of animation media in increasing Arabic vocabulary. This research uses a quantitative approach with a quasi-experimental method. This study uses descriptive analysis, and to determine the effectiveness of the media by comparing the results of the pretest and posttest scores. The results obtained are that the vocabulary animation media is able to improve the ability to master Arabic vocabulary at MI Muhammadiyah 2 Kedungbanteng.